2018
DOI: 10.1097/iae.0000000000001651
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Hypertension and Glaucoma Following Vitrectomy

Abstract: Although the review found increased risk of open-angle glaucoma with pars plana vitrectomy, the studies were heterogenous or inconsistent regarding ocular hypertension and intraocular pressure increase. Larger studies should be conducted in homogenous cohorts of patients undergoing macular surgery, excluding complex conditions such as retinal detachment or diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…There was a significant increase in the IOP in operated eyes between baseline and postoperative day 2, which seems to be due to the effect of surgery itself, such as corneal edema or postoperative inflammation. In addition, as noted in previous studies [17][18][19], the IOP increase in surgically treated eyes could be attributed to the influence of FDP. Furthermore, the IOP significantly decreased between postoperative days 2 and 7 in both eyes, but the degree of descent was higher in the contralateral eyes.…”
Section: Plos Onesupporting
confidence: 71%
“…There was a significant increase in the IOP in operated eyes between baseline and postoperative day 2, which seems to be due to the effect of surgery itself, such as corneal edema or postoperative inflammation. In addition, as noted in previous studies [17][18][19], the IOP increase in surgically treated eyes could be attributed to the influence of FDP. Furthermore, the IOP significantly decreased between postoperative days 2 and 7 in both eyes, but the degree of descent was higher in the contralateral eyes.…”
Section: Plos Onesupporting
confidence: 71%
“…We observed that with intravitreal gas absorption, the lens turns transparent again and only a few lenses cannot be restored to transparent; the pathogenesis for this state of permanent opacity needs further study [ 20 ]. The causes of ocular hypertension after vitrectomy are varied [ 21 ]. It may contribute to laser photocoagulation, combined cataract surgery, severity of postoperative vitreous hemorrhage, and use of expanding gas tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main issues when using Ozurdex as adjuvant to vitrectomy is a possible rise in IOP in the postoperative period. PPV has already been shown as an independent risk factor for the new-onset of open-angle glaucoma after surgery [156,157], and the use of Ozurdex may further boost such a risk. However, this hypothesis is speculative as there is no clear evidence on this matter in the published literature.…”
Section: Evidence Of the Efficacy Of Dex In Vitreoretinal Surgerymentioning
confidence: 98%